Bidirectional DC–DC converter based multilevel battery storage systems for electric vehicle and large‐scale grid applications: A critical review considering different topologies, state‐of‐charge balancing and future trends - Fatih Eroǧlu; Mehmet Kurtoǧlu; Ahmet Mete Vural (IET Renewable Power Generation, 2021)
Abstract The expanding share of renewable energy sources (RESs) in power generation and rise of electric vehicles (EVs) in transportation industry have increased the significance of energy storage systems (ESSs). Battery is considered as the most suitable energy storage technology for such systems due to its reliability, compact size and fast response. Power converters are vital for the integration of batteries into power grid and EVs as they play an active role in both power conversion and battery management. Multilevel converters (MLCs) are types of power converters and attract widespread interest due to their improved power quality, reliability and modularity. There are two main challenges in MLC based battery storage systems (BSSs) which are selecting a proper MLC topology and balancing state‐of‐charges (SOCs) of batteries. Although some research has been carried out on either MLCs or SOC balancing, no single study exists which presents a comprehensive review on MLC based BSSs for large‐scale grid and EV applications. This paper begins by reviewing several major battery storage technologies that are utilised in MLC based BSSs. Later on, a systematical review of commonly used and recently proposed MLC topologies for BSSs are provided along with different control schemes for MLCs by specifically focusing on SOC balancing techniques. Finally, potential challenges and suggestions for future improvement of MLC based BSSs are addressed.